2010
DOI: 10.1007/s00204-010-0611-z
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation in the mouse liver is affected by methyl deficiency and arsenic in a sex-dependent manner

Abstract: Arsenic, a carcinogen, is assumed to induce global DNA hypomethylation by consuming the universal methyl donor S-adenosylmethionine (SAM) in the body. A previous study reported that a methyl-deficient diet (MDD) with arsenic intake greatly reduced global DNA methylation (the content of 5-methylcytosine) in the liver of male C57BL/6 mice. In the present study, we investigated the DNA methylation level, SAM content, and expression of DNA methyltransferases (DNMTs) in the liver of male and female C57BL/6 mice fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 34 publications
5
54
1
1
Order By: Relevance
“…In our previous study, we measured the 5-mC level of the liver of mice fed a methyl-deficient diet, which has been reported to induce DNA hypomethylation, 51 by the precise LC/ESI-MS method, and found that 5 mo of feeding with methyl-deficient diet reduced the 5-mC level by 3.6% in the liver genome of male mice. 15 This study demonstrated that the 5-mC level is changed by up to 11.2% in a day and the deviation is thought to be substantial. On the other hand, we could not find the quantitative difference of DNMT3B protein between ZT 0 and 8 by western blotting analysis (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In our previous study, we measured the 5-mC level of the liver of mice fed a methyl-deficient diet, which has been reported to induce DNA hypomethylation, 51 by the precise LC/ESI-MS method, and found that 5 mo of feeding with methyl-deficient diet reduced the 5-mC level by 3.6% in the liver genome of male mice. 15 This study demonstrated that the 5-mC level is changed by up to 11.2% in a day and the deviation is thought to be substantial. On the other hand, we could not find the quantitative difference of DNMT3B protein between ZT 0 and 8 by western blotting analysis (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…We previously reported that Dnmts mRNA expression in adult mouse liver can vary with diet and according to gender, in combination with chronic arsenic exposure. 15 We have further reported a dynamic change in Dnmt3b mRNA expression in mouse liver between the morning and the afternoon. 15 These findings suggest a novel regulatory mechanism of Dnmt3b linked to clockwork.…”
Section: Diurnal Variations Inmentioning
confidence: 70%
See 3 more Smart Citations